Safety and efficacy of l‐methionine produced by fermentation with Corynebacterium glutamicum KCCM 80184 and Escherichia coli KCCM 80096 for all animal species. (3rd December 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The European Commission asked EFSA for an opinion on the safety for the target animals, consumer, user and the environment and on the efficacy of l ‐methionine produced by fermentation with Corynebacterium glutamicum KCCM 80184 and Escherichia coli KCCM 80096 for all animal species. The two producing microorganisms were obtained by genetic modification. l ‐Methionine is intended to be used in feed or water for drinking for all animal species and categories. Neither viable cells of the production strains, nor their recombinant DNA were detected in the final product. The additive does not pose any safety concern associated with the genetic modification of the production strains. l ‐methionine produced by C. glutamicum KCCM 80184 and E. coli KCCM 80096. The additive is considered safe for the target species, for the consumer and for the environment. l ‐Methionine produced by C. glutamicum KCCM 80184 and E. coli KCCM 80096 is considered not toxic by inhalation, non‐irritant to skin or eyes and not a dermal sensitiser. Regarding the use in water, the FEEDAP Panel reiterates its concerns over the safety of l ‐methionine for target species when administered via water for drinking owing to the risk of nutritional imbalances and hygienic reasons. l ‐Methionine produced by C. glutamicum KCCM 80184 and E. coli KCCM 80096 is considered as an efficacious source of the essential amino acid l ‐methionine for non‐ruminant animal species. For the supplemental l ‐methionine to be as efficacious in ruminants as in non‐ruminant species, it would require protection against degradation in the rumen.